The Impact of Oil and Gas Resources In the Arctic on the Development of the Transport System in the Region - V. I. Salygin (MGIMO University Press, 2015)
One of the main problems of the Russian economy today is the development of the Arctic region. Given the key role of the energy sector in the economic balance of the country, as well as the problem of exhaustion of hydrocarbon resources, the Arctic is of particular interest from an economic and geopolitical point of view, ensuring the energy security of Russia. Active development of the region leads to the development of transport infrastructure, which is one of the priorities of Russia's energy policy. The issue of transportation plays a leading role in the context of the development of Arctic resources and involves a number of tasks. The first step is to ensure the safety of navigation in the Arctic ice. Also existing infrastructure needs substantial upgrading, as well as construction of new facilities (including ports, railways, roads, etc.). Of particular note is a unique transcontinental route - the Northern Sea Route. There is a need to modernize the Arctic Fleet, including the construction of modern icebreakers of the Arctic class. The current state of the port system, which does not fully meet the latest international standards, is of crucial importance as well. In addition, along the route the development of railway infrastructure is required. In addition, there is the problem of underdevelopment of the road network, which leads to a re-run and lack of access of some are as to the road network of Russia. Thus, the development of hydrocarbon resources in the Arctic region contributes to the development of infrastructure of the transport system in the region and, consequently, its economic development that contributes to the economic well-being of the country as a whole.